The impact of Petronas Independence Day TV Commercials among teenagers - Nur Akma Halili; Md Nagib Padil; Mohd Khairul Azahari Abd Rani; Khairul Anuar Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2016)
Advertisements through the use of electronic media such as TV ads are a particularly effective communications tools to convey more effective services to the community. The objective of this research is to examine the Petronas Independence Day TV Commercials as Public Service Announcements (PSA) in creating awareness and self-esteem among teenager. Self-esteem among the society is developed with the availability of effective advertisements through the messages and the values embedded in it. Advertisement is a form of communication that is effective in spreading the reflection of the identity, the culture and the society of Malaysia. Meanwhile, TV ads or TV Commercial is the best medium to convey, persuade and can communicate with audience in term of people moral value, human’s lifestyle, attitude, behaviour, culture and etc.